2012
DOI: 10.1021/ma3017597
|View full text |Cite
|
Sign up to set email alerts
|

Linear Gradient Quality of ATRP Copolymers

Abstract: The linear gradient quality and the control over chain length and endgroup functionality in the copolymerization of acrylates, methacrylates, and styrenes via atom transfer radical polymerization (ATRP) are evaluated by detailed kinetic Monte Carlo simulations with explicit tracking of macromolecules. In all simulations, diffusional limitations on termination are taken into account. The linear gradient quality is characterized by a linear gradient deviation ⟨GD⟩ ranging between 0 and 1. For a ⟨GD⟩ value of 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
191
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(196 citation statements)
references
References 62 publications
5
191
0
Order By: Relevance
“…It has been indicated that the outcome of the ARGET ATRP is very sensitive to the initial concentrations. In particular, the amount of reducing agent has to be selected carefully, taking into account a trade-off between polymerization rate and livingness [29][30][31][32]. Moreover, by switching to continuous operation, a more industrial attractive process can be obtained [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that the outcome of the ARGET ATRP is very sensitive to the initial concentrations. In particular, the amount of reducing agent has to be selected carefully, taking into account a trade-off between polymerization rate and livingness [29][30][31][32]. Moreover, by switching to continuous operation, a more industrial attractive process can be obtained [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…However, in these kinetic studies, in which no explicit calculation of the copolymer composition is included, the fed/semi-batch addition of comonomer is accompanied by a low polymerization rate, a rather high dispersity and a relatively low livingness. As indicated in a recent kMC study of Van Steenberge et al [26] low dipersities are required for controlled linear gradient synthesis and it can therefore be expected that under the reported literature conditions still relatively high <GD> values are obtained, despite the linear relation between F 1,inst and x overall .…”
Section: Multi-component Fed-batch Procedures For Addition Of Conventimentioning
confidence: 85%
“…Except for reactions involving conventional radical initiator fragments, these intrinsic parameters are taken from a previous kinetic study on the related "normal" ATRP system [26]. For simplicity, a constant conventional radical initiator efficiency of 0.70 [22] is used and the activation/deactivation kinetic parameters related to the conventional radical initiator are taken equal to those of the secondary species.…”
Section: Kinetic Modelmentioning
confidence: 99%
See 2 more Smart Citations